Analysis of the Quality of Sustainability and Governance Disclosure in SR Reports: A Study of 51 Indonesian Public Companies Based on POJK 51 - Nurdialy, Mela; Wijaya, Henryanto (Law and Economics, 2025)
Sustainability reports (SR) are an important tool for demonstrating corporate transparency and accountability on environmental, social, and governance (ESG) issues. This study evaluates the quality of sustainability disclosure in four key dimensions: sustainability strategy, sustainability governance, sustainability performance, and independent verification. The evaluation was conducted on 51 Indonesian public companies from the energy, raw materials, manufacturing, and financial sectors, using over 40 indicators developed from the provisions of POJK 51 of 2017. The analysis results show that the energy sector consistently achieved the highest scores across all dimensions, reflecting high regulatory and social pressures. Conversely, the financial and industrial sectors lagged behind, particularly in the strategy and verification dimensions, indicating weak integration of sustainability principles into corporate governance. The governance dimension revealed symbolic disclosures that have not yet addressed substantive aspects such as ESG risk management and competency development. Meanwhile, only 31% of companies included independent assurance statements. This finding underscores the need to strengthen the integration of sustainability into governance systems and improve the quality and credibility of reports. The analysis is supported by legitimacy theory, accountability theory, stakeholder theory, and recent empirical literature.